2020
DOI: 10.18203/2320-1770.ijrcog20201230
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia among school going adolescent girls in rural area of Pune, Maharashtra, India

Abstract: Background: Anemia is like the tip of an iceberg, as majority of anemic subjects are asymptomatic. Low iron diet for longer period perpetuates an inter-generational cycle of anemia, anemic women giving birth to anemic children. This situation is more acute in rural area due to their dietary habits, illiterate parents, socio-economic status, misconception about food, religions belief, menstruation and physical activity. Methods: This descriptive cross-sectional study was conducted in rural field practice area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
2
3
1
Order By: Relevance
“…About 62.5% adolescent girls were anemic in the present study, which is in consensus with the findings of different studies wherein anemia prevalence is documented from 59% to 65.7%. 4,11,12 On the other hand, in contrast to our study findings Chandrakumari et al, 2 and Bodat et al, 13 reported comparatively lower and higher prevalence of 48.3% and 87.6%, respectively, among the adolescent girls in their study.…”
Section: Discussioncontrasting
confidence: 94%
“…About 62.5% adolescent girls were anemic in the present study, which is in consensus with the findings of different studies wherein anemia prevalence is documented from 59% to 65.7%. 4,11,12 On the other hand, in contrast to our study findings Chandrakumari et al, 2 and Bodat et al, 13 reported comparatively lower and higher prevalence of 48.3% and 87.6%, respectively, among the adolescent girls in their study.…”
Section: Discussioncontrasting
confidence: 94%
“…[16,17]. The mean±SD HB levels of the girls were found to be 10.1±1.71g/dl and was similar to the other studies in India in this age group [15,18]. Clinical signs, paleness of (eyes, lips, tongue, skin, nails, gums) reported among AG were statistically significant (p<0.005) to the prevalence of anaemia.…”
Section: Discussionsupporting
confidence: 80%
“…HAZ was not significant but there was trend(p=0.089). BMI, there was a significant association with anaemia prevalence (p<0.005) which coincided with the study [15]. 88% of anaemic girls had attained menarche.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…[ 13 ] Bodat et al . [ 14 ] observed that the overall prevalence of anemia among school-going adolescent girls in a rural area of Pune, Maharashtra was 87.60%, with 47.06%, 52.48%, and 0.46% of the girls having mild, moderate, and severe anemia, respectively.…”
Section: Discussionmentioning
confidence: 99%